2022
DOI: 10.3390/s22186749
|View full text |Cite
|
Sign up to set email alerts
|

A Semantic Data-Based Distributed Computing Framework to Accelerate Digital Twin Services for Large-Scale Disasters

Abstract: As natural disasters become extensive, due to various environmental problems, such as the global warming, it is difficult for the disaster management systems to rapidly provide disaster prediction services, due to complex natural phenomena. Digital twins can effectively provide the services using high-fidelity disaster models and real-time observational data with distributed computing schemes. However, the previous schemes take little account of the correlations between environmental data of disasters, such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The existing research shows that the new generation of intelligent technology has been applied to solve the EMCI problem [53]. A DT platform connects ubiquitous intelligent terminals, integrates ICTs such as big data and IoT, and fully uses disaster data, which provides a feasible way to effect EMCI [54]. The construction of DT in EMCI generally consists of five layers: a physical layer, data layer, service layer, DT layer, and user-interaction layer, as shown in Figure 8.…”
Section: Dt System Architecture For Emcimentioning
confidence: 99%
“…The existing research shows that the new generation of intelligent technology has been applied to solve the EMCI problem [53]. A DT platform connects ubiquitous intelligent terminals, integrates ICTs such as big data and IoT, and fully uses disaster data, which provides a feasible way to effect EMCI [54]. The construction of DT in EMCI generally consists of five layers: a physical layer, data layer, service layer, DT layer, and user-interaction layer, as shown in Figure 8.…”
Section: Dt System Architecture For Emcimentioning
confidence: 99%
“…Kwoo et al (2022) suggested that digital twins could be used to enhance high-fidelity disaster models and real-time observational environmental data, with distributed computing schemes. It would substantially decrease the disaster prediction time [40].…”
Section: Sustainability As Topic In the Metaverse-topic Publicationsmentioning
confidence: 99%